Implementasi Sistem Informasi Raport Online Berbasis Website untuk Meningkatkan Efisiensi dan Aksesibilitas Pengelolaan Nilai Siswa di Sekolah Menengah Pertama - Jarti, Nanda; Suryadi, Agus; Andriawan, Arya (LPPM Universitas Ibnu Sina, 2024)
The current method of recording student grades at Kallista School is not fully computerized. Grades are manually entered into report books, which, when errors or mistakes occur, result in disorganized report content. Additionally, the extensive and complex recording of student data, attendance, class schedules, subjects, and grades in the junior high school's ledger book poses difficulties in data processing in case of errors in both recording and managing large-scale data. Therefore, it is imperative for the school to provide a service that offers rapid, easy, practical, and efficient access to report card information for students and their parents or guardians. This information system is designed as a website using PHP programming language and MySQL database. The implementation of this online report information system facilitates the tasks of teachers and administrative staff in fulfilling their responsibilities, while enabling parents to easily, quickly, and economically access school report information from anywhere, anytime, transcending geographical and temporal constraints.